Promoting Peaceful Sleep: Exploring the Therapeutic Potential of Microemulsion with Cedarwood and Passion Flower Essential Oils for Insomnia Relief - Raksha, Goswami; Kumar, Jain Neetesh (Journal of Neonatal Surgery, 2025)
Aim: This research explores the pharmacological efficacy of polyherbal microemulsions specifically designed to alleviate insomnia. Method: Carefully selected herbs with sedative, anxiolytic, and sleep-enhancing properties were blended to formulate polyherbal microemulsions. An essential step in formulation involved optimizing the proportions of oil, water, surfactant, and co-surfactant to ensure stability and enhance active ingredient delivery. The system's suitability for systemic use was validated through physicochemical analysis, including droplet size and zeta potential assessment. In vivo evaluations using insomnia-induced animal models revealed improvements in sleep-related parameters such as sleep latency, duration, and quality. Result: The results contribute to growing evidence supporting the therapeutic potential of polyherbal microemulsions for insomnia treatment. By harnessing the synergistic properties of herbal constituents in an optimized delivery system, these formulations offer a holistic method to reestablish sleep patterns while minimizing adverse effects. Further clinical trials are necessary to validate these findings and encourage the integration of such formulations into mainstream insomnia therapies